Portable-CELLxGENE: standalone executables of CELLxGENE for easy installation - George T. Hall (GigaByte)
Biologists who want to analyse their single-cell transcriptomics dataset must install and use specialist software via the command line. This is often impractical for non-bioinformaticians. Whilst the popular CELLxGENE software provides an intuitive graphical interface to facilitate analysis outside the command line, its server-side installation and execution remain complex. A version that is easier to install and run would allow non-bioinformaticians to take advantage of this valuable tool without needing to use the command line. This work introduces Portable-CELLxGENE, a standalone distribution of CELLxGENE that can be installed via a graphical interface. It contains an easy-to-use extension of the CELLxGENE-Gateway Python package to allow the analysis of multiple datasets. This tool enables non-bioinformaticians to carry out simple analyses independently.